2013
DOI: 10.1021/np4005135
|View full text |Cite
|
Sign up to set email alerts
|

Hinokitiol Inhibits Cell Growth through Induction of S-Phase Arrest and Apoptosis in Human Colon Cancer Cells and Suppresses Tumor Growth in a Mouse Xenograft Experiment

Abstract: Hinokitiol (1), a tropolone-related natural compound, induces apoptosis and has anti-inflammatory, antioxidant, and antitumor activities. In this study, the inhibitory effects of 1 were investigated on human colon cancer cell growth and tumor formation of xenograft mice. HCT-116 and SW-620 cells derived from human colon cancers were found to be similarly susceptible to 1, with IC50 values of 4.5 and 4.4 μM, respectively. Compound 1 induced S-phase arrest in the cell cycle progression and decreased the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 34 publications
4
43
0
Order By: Relevance
“…3-HT significantly inhibited the expression of cyclin E1, cyclin A2 and CDK2; thus, preventing the formation of cyclin E-CDK2 and cyclin A2-CDK2 complexes, which play pivotal role in the initiation and progression of the S phase (33), ultimately leading to S phase arrest. The results were in accordance with previous studies that natural compounds induced S phase arrest by inhibiting the expression of cyclin E, cyclin A2 and CDK in different types of human cancer cells (27,28). A previous study reported that h-PNAS-4 induced S phase arrest in ovarian cancer cells via activation of the Cdc25A-Cdk2-cyclin E/cyclin A pathway, the expression of cyclin E and cyclin A were upregulated while Cdc25A was inhibited (34).…”
Section: Discussionsupporting
confidence: 93%
“…3-HT significantly inhibited the expression of cyclin E1, cyclin A2 and CDK2; thus, preventing the formation of cyclin E-CDK2 and cyclin A2-CDK2 complexes, which play pivotal role in the initiation and progression of the S phase (33), ultimately leading to S phase arrest. The results were in accordance with previous studies that natural compounds induced S phase arrest by inhibiting the expression of cyclin E, cyclin A2 and CDK in different types of human cancer cells (27,28). A previous study reported that h-PNAS-4 induced S phase arrest in ovarian cancer cells via activation of the Cdc25A-Cdk2-cyclin E/cyclin A pathway, the expression of cyclin E and cyclin A were upregulated while Cdc25A was inhibited (34).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, It has also been reported to regulate tumor growth and metastasis, β-thujaplicin’s antitumor effects have been investigated in a variety of cancer models, including models of melanoma,breast cancer,lung cancer,colon cancer,prostate cancer, and oral cancer [3335,38,46,47]. Some studies have shown that β-thujaplicin can inhibit cancer cell proliferation by inducing the p53-independent DNA damage response, S or G1 cell cycle arrest [33,34,48]. However,we found β-thujaplicin can inhibit HR repair through regulating the recruitment of RAD51 rather than inducing cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Hinokitiol has been reported to have applications in regulating several biological activities including anti-inflammation [23], anti-bacterial [24], anti-fungal [25], and anti-viral activities [26]. It has also been shown to have anti-proliferative effects in various cancer cell lines including melanoma [27], prostate carcinoma [28], oral cancer [22] and colon cancer cells [29]. However, the effects of hinokitiol on lung adenocarcinoma cells and the mechanisms underlying its effects have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%